Multiple Personality and the Dependence on an Intimate Ambience ( Between Luigi Pirandello and Ernest Koliqi) - Dani, Alva (Richtmann Publishing, 2012)
The author of this article aims at analysing the motif of multiple personality which emerges as a consequence of themodern man crisis. By making a comparison with Luigi Pirandello and referring to short stories by Ernest Koliqi, she intends tomake known the presence of this phenomenon even in the Albanian literature of the years ’20-’30. This is no accidentalcomparison, for Ernest Koliqi was an Albanian writer who was educated from early age in the Italian colleges and later on in theItalian Universities. He worshiped Italian literature and believed in its educational power. With his philosophical way of thinkingand deep psychological and spiritual analysis, Pirandello influenced Koliqi’s work and it can be said that he elaborated Koliqi’sway of reflecting and art making. This is best illustrated through the analysis of an individual’s personality, who does not have acertain identity any more, but only a conflict with himself/herself and the ambience that surrounds him/her, which will inevitablypush him/her toward a fatal solution.